Reactive oxygen species contribute to delirium-like behavior by activating CypA/MMP9 signaling and inducing blood-brain barrier impairment in aged mice following anesthesia and surgery - Liu, Li-fang; Hu, Yun; Liu, Yi-nuo; Shi, De-wen; Liu, Chang; Da, Xin; Zhu, Si-hui; Zhu, Qian-yun; Zhang, Ji-qian; Xu, Guang-hong (Frontiers in Aging Neuroscience, 2022)
Postoperative delirium (POD) is common in the elderly and associated with poor clinical outcomes. Reactive oxygen species (ROS) and blood-brain barrier (BBB) damage have been implied in the development of POD, but the association between these two factors and the potential mechanism is not clear. Cyclophilin A (CypA) is a specifically chemotactic leukocyte factor that could be secreted in response to ROS, which activates matrix metalloproteinase 9 (MMP9) and mediates BBB breakdown. We, therefore, hypothesized that ROS may contribute to anesthesia/surgery-induced BBB damage and delirium-like behavior via the CypA/MMP9 pathway. To test these hypotheses, 16-month-old mice were subjected to laparotomy under 3% sevoflurane anesthesia (anesthesia/surgery) for 3h. ROS scavenger (N-acetyl-cysteine) and CypA inhibitor (Cyclosporin A) were used 0.5 h before anesthesia/surgery. A battery of behavior tests (buried food test, open field test, and Y maze test) was employed to evaluate behavioral changes at 24 h before and after surgery in the mice. Levels of tight junction proteins, CypA, MMP9, postsynaptic density protein (PSD)-95, and synaptophysin in the prefrontal cortex were assessed by western blotting. The amounts of ROS and IgG in the cortex of mice were observed by fluorescent staining. The concentration of S100β in the serum was detected by ELISA. ROS scavenger prevented the reduction of TJ proteins and restored the permeability of BBB as well as reduced the levels of CypA/MMP9, and further alleviated delirium-like behavior induced by anesthesia/surgery. Furthermore, the CypA inhibitor abolished the increased levels of CypA /MMP, which reversed BBB damage and ameliorated delirium-like behavior caused by ROS accumulation. Our findings demonstrated that ROS might participate in regulating BBB permeability in aged mice with POD via the CypA/MMP9 pathway, suggesting that CypA may be a potential molecular target for preventing POD.